Plant acoustic frequency technology control system to increase vegetative growth in red-lettuce - Yusuf Hendrawan; Adamsyah Harika Putra; Sumardi Hadi Sumarlan; Gunomo Djoyowasito (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The application of plant acoustic frequency technology (PAFT) can spur plant growth, increase productivity, immune system, quality, and extend the shelf life of agricultural products after harvest. The application of sound waves in plants can stimulate the opening of the stomata to optimally absorb nutrients and water. This study aims to determine the effect of frequency and time of PAFT exposure by utilizing Javanese gamelan traditional music on the vegetative growth of red-lettuce (Lactuca sativa var.). Javanese gamelan music used was titled Puspawarna with variations in the frequency of 3-5, 7-9, and 11-13 kHz. The variation of exposure time of sound waves was 1, 2, and 3 hours. PAFT exposure was given routinely in the morning and evening. The results of this study indicated that the best treatment was at 3-5 kHz with an exposure time of 2 hours. This treatment gave a significantly better effect when compared to plants without PAFT. The best combination of frequency and time of PAFT exposure produced 10 leaves, plant height of 9.4 cm, wet weight of 4 g, dry weight of 0.22 g, leaf area of 27.19 cm2, leaf red mean of 63, and stomata opening width of 145.44~206.59 µm.